THE IMPLEMENTATION OF AUTOCRATIC AND CHARISMATIC LEADERSHIP MODEL AT ISLAMIC HIGHER EDUCATION IN AN ISLAMIC BOARDING SCHOOL ENVIRONMENT (STUDY AT STAI DDI MANGKOSO) - Arif, Muthahhir; Ramli, Mansyur; Mus, Abdul Rahman; Bunyamin, Andi (Program Pascasarjana, UIN Alauddin Makassar, 2021)
Leadership in the pesantren environment has an interesting dynamic. This environmental base is generally religious with leadership that is patronized by religious leaders such as kyai, then stereotypes are built in people's understanding that the kyai is the sole leader in a pesantren, or it is common for every pesantren to be cared for and led by a kyai who makes the position of this leader the single colour of leadership. in the pesantren environment. This research is interactive qualitative research with descriptive quantitative analysis. Data retrieval used questionnaires, historical data that already exists. This study used data collection techniques using observation, questionnaire, interview, and documentation techniques. The validity of the research data was checked by using triangulation. The results show that the autocratic leadership model sees the organization as a mechanical tool and all decisions are in the hands of the leader, while the charismatic leadership model can include believing the truth from the leader, accepting what the leader says without asking, carrying out tasks based on the awareness and direction of the leader, encouraging employees in achieving the mission of the institution, encouraging employees to improve performance.